COMPOSITE FLOUR MIXTURES IN THE PRODUCTION OF GINGERBREAD PRODUCTS - KOKOSH, MARYNA; SEMA, OKSANA; SACHKO, ANASTASIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
One of the approaches to improving product quality and enhancing the nutritional structure of the population is the incorporation of novel, unconventional plant-based raw materials into the diet. These materials contain balanced complexes of proteins, lipids, minerals, vitamins, and other essential compounds. An innovative direction in the development of the flour-based confectionery industry is the production of new baked goods utilizing flour blend compositions that include flour from various cereals, legumes, and oilseeds.This study presents the results of research on the formulation of choux gingerbread using composite flour mixtures to obtain an enriched product with increased levels of essential amino acids, macro- and micronutrients, and other biologically active components. To impart specific properties to the gingerbread products, a partial replacement of wheat flour with chickpea flour was proposed. Due to its amino acid composition and fiber content, legume flour serves as an ideal ingredient for enhancing the nutritional value of confectionery products. Additionally, chickpea flour is a gluten-free product that contains dietary fiber, which contributes to gut health regulation.The nutritional value of the baked gingerbread was assessed, revealing that the inclusion of chickpea flour in its production led to an increase in nutritional quality, enrichment with proteins, fats, and amino acids, and a reduction in caloric content by 6–9.3% compared to gingerbread made according to the traditional recipe. Structural and mechanical analysis indicated a deterioration in product rise and water absorption capacity, yet an increase in baking loss by 1.5 times was observed. The addition of chickpea flour also resulted in a 35% decrease in alkalinity compared to the control sample, along with a slight reduction in moisture content.
Keywords: custard gingerbread; chickpea flour; non-traditional raw materials